Neo-Weberian State in the context of the global economic crisis (Economic and Political Thought, 2016)
The main aim of the article is to present the Neo-Weberian State in thecontext of changes in the perception of the role of a state in the economy dueto the global economic crisis that started at the turn of 2007. As a result of thecollapse of the mortgage market in the United States, which eventually led tothe collapse of many economies in the world, some experts began to see theneed to increase the role of a state, weakened as a result of popularizationof new solutions typical of the trend of New Public Management and NewPublic Governance. One proposal that has gained importance is the conceptof the Neo-Weberian State proposed by C. Pollitt and G. Bouckaert. Theirsolution combines the best aspects of these two models with the classicalWeberian bureaucracy assuming the central coordinating role of the statein countering global challenges. In the article, the author presents some ofthe causes of the outbreak of the global economic crisis, referring to theJ.M. Keynes’ concept of ‘animal spirits’, which G. Akerlof and R. Schilleranalysed based on the current problems of global economies. Next, the authorassesses to what extent the Neo-Weberian State is a response to the presenceof ‘animal spirits’ in the economy and shows example solutions in harmonywith the proposal of C. Pollitt and G. Bouckaert in the United States and theEuropean Union.